Dimensions of Sutism in Strengthening the Value of Religious Moderation in Indonesia Buya Arrazy's Perspective - Putri Pratiwi Listianingrum; Alifarose Syahda Zahra; Ubaidillah (Pascasarjana IAIN Metro, 2024)
In religious moderation, in fact, a major aspect strengthens the key to creating tolerance and harmony that must be mutually maintained. With the creation of peace, each of the religious communities can treat other people with respect. Religious moderation is a middle way in the midst of religious diversity in Indonesia. Indonesia which has the largest number of muslims in te world is a imprtant example of islamic moderation. In islam moderation is a teaching. Respect for each other in social settings, not in worship, is what we mean when we talk about tolerance is the most important factor. The purpose of this research is to explore a religious moderation that should be developed as a joint commitment to maintain a balance where every tribe, ethnicity and cultural maintain harmony with each other. Researchers use the library research method. The result of this paper are first, the moderation of the core teachings in the Islamic population in Indonesia. Second, tolerance will have a positive attitude between religions, races, etc. third, the existence of religious moderation will strengthen a multiculturalism.